Morphology and optical properties of CdS thin films prepared by Physical Vapor Deposition method - Vakaliuk, I.V.; Yavorskiy, R.S.; Nykyruy, L.I.; Naidych, B.P.; Yavorskyy, Ya.S. (Physics and Chemistry of Solid State, 2022)
The optical properties of cadmium sulfide thin films obtained by thermal evaporation in vacuum were studied. The stoichiometric compositions of the binary compound previously synthesized from high-purity powders of the initial components were used. Films of different thicknesses deposited on a glass substrate were investigated using scanning electron microscopy and absorption coefficient was defined by the Swanepoel method. It was found that with increasing film thickness, surface formations decrease and at a thickness of 1 μm the film surface is continuous. It is determined that thin films of cadmium sulfide have optimal optical parameters for use as photovoltaic buffer layer. All the obtained films except the film with a thickness of 1215 nm show the usual interference pattern in the reflection spectra.